Nghiên cứu các yếu tố tác động đến sự sẵn sàng sử dụng hệ thống đào tạo trực tuyến của giáo viên các trường trung học phổ thông ở khu vực Đồng bằng sông Cửu Long: trường hợp nghiên cứu UEH Global Learning - Nguyễn, Lý Kiều Chinh; Phan, Thị Thúy Kiều (Tạp chí Giáo dục, 2024)
UEH Global Learning online training system is a community project of the University of Economics Ho Chi Minh City that aims to share and transfer experience in free digital transformation in teaching and learning activities for high school teachers, especially in the Mekong Delta region. To ensure the effective use of this system, it is necessary to clearly understand the factors that impact teachers' willingness to use. Those are the factors with relatively high importance and relatively low effectiveness. The research study is based on the survey results of 195 high school teachers in the Mekong Delta region who participated in the UEH Global Learning training class, conducting quantitative analysis using the PLS-SEM model identified 9 factors. The impacts include: (1) Information quality, (2) System quality, (3) Service quality, (4) Usefulness, (5) Ease of use, (6) Attitude, ( 7) Intention, (8) Social Influence and (9) Satisfaction. In addition, the researcher used the IMPA method to identify two influential factors with relatively high importance and relatively low performance: Attitude and Intention. The research results have practical implications to further improve the effectiveness of using UEH Global Learning in teaching practice.